Aplicación web para la comercialización de productos de la asociación “Iniciativa Turística Colaguango - San Luis” perteneciente a la parroquia Belisario Qquevedo. - Angueta Carrión, Cristian Mauricio (2020)
The present project consisted of developing a web application for the commercialization of products of the association "Iniciativa Turística Colaguango-San Luis", where the lack of support from local and provincial administrations was evidenced, when trying to increase the sales of their products and offer them inside and outside the community, this triggered the producers to have a negative vision that this type of undertaking generates economic opportunities for more inhabitants of the area, in addition to not having the perception of starting more projects in the future related to the activities that they carry out in the association. The aforementioned are weaknesses that it brings from the hand, not having a technological means, which automates the manual processes that producers carry out when offering and selling their products, which triggers difficulties such as disorderly, outdated and redundant information, lack and insufficient important reports, loss of time and resources, in the activities carried out in the association. Thus, the development of the project was oriented on information collected in scientific sources and reliable indexed journals, simultaneously applying methods that made it possible to synthesize the themes related to the technological proposal. Research techniques, such as surveys and interviews, were also applied to collect information that helped identify the problem and needs, in addition to determining the requirements and functionalities of the web application. For the development of the web application, the Scrum methodology and the unified modeling language were used, achieving thirty-one fully functional actions, the same ones that the users of the system (administrator, producers, customers and providers) perform together. In the case of the development of the web application, computer tools were used such as: PHP7 programming language, MySQL database manager, JavaScript interpreted programming language, HTML markup language, application programming interface such as: PayPal API, Google API Maps, WhatsApp API, also libraries such as: AlertifyJS, Bootstrap, PHPMailer, Select2, Ionicons, as well as the Sublime Text integrated development environment, DB Designer visual database system and Rapidminer data science platform. As soon as the web application was hosted on a web server, this service is provided by the EcuaHosting company. In this way, through the implementation of the application in the association, the great satisfaction of the users was found to have a technological means, this is clearly evident in the help that was provided to the establishment by replacing the daily way of offering and selling products, In addition, a great workload was released to users as they handle real, ordered and updated information on each of their activities.